Anti-oxidant Activity of Methanol Extracts of Arum maculatum L. and Physalis peruviana L. Plants - Mohammed, Zahraa H.; Ibraheem, Ruqaya M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Total flavonoid contents, reductive ability and radical scavenging activity were studied in the methanol extracts of Arum maculatum L. and Physalis peruviana L. The results revealed that A. maculatum extract had total flavonoids of 535.3±109.9 µg/ml, which was significantly higher than the recorded flavonoids in P. peruviana extract (352.0±12.7 µg/ml). Assessment of reductive ability revealed that both extract were effective in such activity and concentration-dependent. The highest absorbance was found at the concentration 0.64 mg/ml of A. maculatum methanol extract (0.929±0.006), which was significantly higher (P ≤ 0.05) than the corresponding concentration of P. peruviana extract (0.850 ± 0.050) or trolox (0.278±0.010), but the second extract also showed a significant increased absorbance compared to trolox. The results of DPPH radical scavenging activity confirmed those of reductive ability, and again the highest concentration (0.500 mg/ml) of both extracts (A. maculatum and P. peruviana) recorded the best radical scavenging activity (93.33±0.58 and 95.33±2.52%, respectively), which was significantly higher than that of vitamin C (64.67±5.03%). In conclusion, both extracts can be considered as important medicinal plants that have the potential of anti-oxidant and free-radical scavenging activities.